16.1k views
12 votes
What is the balanced equation for the unbalanced equation
Mg(s) + O2(g) -> MgO(s)

1 Answer

5 votes

Answer:

2Mg(s) + O2(g) -> 2MgO(s)

Step-by-step explanation:

Mg(s) + O2(g) -> MgO(s)

1 Mg atom and 2 O atoms on the reactant side | 1 Mg atom and 1 O atom on the product side.

add a 2 infront of MgO to balance the O atoms:

Mg(s) + O2(g) -> 2MgO(s)

Now there's 1 Mg atom and 2 O atoms on the reactant side | 2 Mg atoms and 2O atons on the product side.

Now add a 2 infront of the Mg on the ractant side:

2Mg(s) + O2(g) -> 2MgO(s)

Now there are 2 Mg and 2 O atoms on both the reactant and product sides.

User Valery Miller
by
4.7k points